Implementation of assessment for learning to improve students’ cognitive learning outcomes in the concept of chemical bonding - Siti Mutmainah; Muchlis Muchlis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The purpose of this study is to describe the implementation of Assessment for Learning-based Learning, student activities, improving cognitive learning outcomes, and student responses after applying Assessment for Learning-based education. The type of research is a pre-experimental research design with one group pretest-posttest design. The research subjects were 39 high school students. The Assessment for Learning-based Learning implementation during the first, second and third meetings was very well carried out with 93.6%, 94.9%, and 98.6%, respectively. The students did suitable activities for three meetings by assessing learning principles with 94.9%, 92.9%, and 97.0%. After implementing Assessment for Learning-based Learning, the increase in student learning outcomes was as many as 92.3% of students in the high n-gain category. 7.7% of students in the medium n-gain category and 94.8% passed classical learning completeness. Student responses to Assessment for Learning-based Learning get a good response with a percentage of 89%. In conclusion, Assessment for Learning-based Learning can improve the learning outcomes of 10th grade students on the chemical bonding material.